Lessons from the PROTECT-CH COVID-19 platform trial in care homes - Bath, Philip M; Ball, Jonathan; Boyd, Matthew; Gage, Heather; Glover, Matthew; Godfrey, Maureen; Guthrie, Bruce; Hewitt, Jonathan; Howard, Robert; Jaki, Thomas; Juszczak, Edmund; Lasserson, Daniel; et al. (Health technology assessment (Winchester, England), 2025)
Coronavirus disease-2019 was associated with significant mortality and morbidity in care homes in 2020-1. Repurposed antiviral drugs might reduce morbidity and mortality through reducing viral transmission, infection, replication and inflammation. We aimed to compare the safety and efficacy of potential antiviral drugs in care home residents. We designed a cluster-randomised, open-label, blinded end-point platform trial to test drugs in a postexposure prophylaxis paradigm. Participants aged 65+ years from United Kingdom care homes, with or without nursing, were eligible for participation. Care homes were to be allocated at random by computer to administer 42 days of antiviral agent (ciclesonide or niclosamide) plus standard care versus standard care alone to residents. The primary outcome at 60 days after randomisation comprised the most serious outcome, which was defined as all-cause mortality, all-cause hospitalisation, severe acute respiratory syndrome coronavirus 2 infection or no infection. Analysis would be by intention to treat using ordinal logistic regression. Other outcomes included individual components of the primary outcome, transmission, plus health economic and process evaluation outcomes. The planned sample size was 300 care homes corresponding to 9600 residents. With ~40% of care homes predicted to develop an outbreak during the trial, we needed to recruit 750 homes/24,000 residents. We initiated the trial including protocol, approvals, insurance, website, database, data algorithms, intervention selection and training materials. We built a network of principal investigators and staff (91) and care homes (299) to support the trial. However, we never contracted care homes or general practitioners since the trial was stopped in September 2021, as vaccination in care homes had significantly reduced infections. Multiple delays significantly delayed the start date, such as: (1) reduced prioritisation of pandemic trials in 2021; (2) cumbersome mechanisms for choosing the investigational medicinal products; (3) contracting between National Institute for Health and Care Research and the investigational medicinal product manufacturers; (4) publicising the investigational medicinal products; (5) identification of sufficient numbers of care homes; (6) identification and contracting with several thousand general practitioners; (7) limited research nurse availability and (8) identification of adequate insurance to cover care homes for research. Generic challenges included working across the four home nations with their different structures and regulations. The feasibility of contracting between the sponsor and the principal investigators, general practitioners and care homes; screening, consent and treatment of care home residents; data acquisition and the potential benefit of postexposure prophylaxis were never tested. The success of vaccination meant that the role of postexposure prophylaxis of coronavirus disease-2019 in care home residents was not tested. Significant progress was made in developing the infrastructure and expertise necessary for a large-scale clinical trial of investigational medicinal products in United Kingdom care homes. The role of postexposure prophylaxis of coronavirus disease-2019 in care home residents remains undefined. Significant logistical barriers to conducting research in care homes need to be removed urgently before future studies are possible. Further work is required to develop the infrastructure for clinical trials of investigational medicinal products in care homes. Serious consideration should be given to building and then hibernating a pandemic-ready platform trial suitable for care home research. This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number NIHR133443.